PERANAN PEMERINTAH DALAM MENGIMPLEMNTASIKAN KEBIJAKAN PEMBANGUNAN SDM ( DI KELURAHAN TEWAAN KECAMATAN RANOWULU KOTA BITUNG) - Sumuruk, Natalia Anastasya; Lengkong, Florence Daicy; Laloma, Alden (Sam Ratulangi University, 2015)
ABSTARCT: Every good areas of the city to the village level have programs of human resource development to its citizens. but whether the government has implemented its policy implementation is well or not in each region ? So that will impact the results. The purpose of this study was to determine the role of government in implementing human resource development policy in the sub-district Tewaan villages of Bitung city. The method used in this study is a qualitative method , as well as to find the percentage of analytical techniques with the help of the formula P = F / NX100. Data sources and respondents were 14 respondents taken 6 staff employee in the office of the villages 8 community leaders. Data collection using questionnaire and with interview techniques assisted. The results of data analysis showed : The Role of government in the implementation of human resource development policy is positive and highly significant, capable of both high and directed in improving standards of living. Based on the results of these studies concluded that the role of governmnent in implementing human resource development policy in the villages tewaan of bitung city, the government has been able to implement a very good and high quality human resources development policy because it has been as expected and needed by the community. Based on these conclusions suggested : Maintaining implementation pattern of development that has been done, focus on the implementation of human resource development in improving standards of living, continues to establish communication with all level of society in order to support the implementation of development.Keywords : Role, Policy implementation